PENGARUH KOMPETENSI SDM DAN MOTIVASI PEGAWAI TERHADAP PELAKSANAAN PENGAWASAN AMBIEN DI KOTA TANGERANG - Ade Burhanudin; Misbah Nurhafizah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
Tangerang City Government should also intensely monitor the ambient air in the city of Tangerang to improve oversight performed by existing employees in the Environmental Management Agency (BLH). Indeed, at this time the number of employees assigned to conduct surveillance in order to monitor the ambient in Tangerang are quite spacious, very limited, so that not all points that have a high potential of air pollutants can be placed air pollution monitoring tool.On the basis of the above reasoning, the researchers made the following thesis title: "Influence of Competence HR and Employee Motivation of the Implementation Monitoring Ambien in Tangerang.This study used quantitative research methods which belong to the kind of causal. Where that becomes respondents are employees in BPLH Kota Tangerang totaling 39 people, were taken using random random than 44 employees. The hypothesis put forward is suspected there are significant human resource competencies and motivation to conduct monitoring ambient in Kota Tangerang carried out by the Environmental Control. Based on respondents' perception that the research study variables such as: HR competence, motivation and monitoring of the ambient environment Environmental Control Agency Tangerang City showed a good condition, so the researchers suggest in order to maintain. But although in good condition, results of this study, the effect of HR competence variables and variable motivation to ambient monitoring does not become dominant. Therefore, efforts to increase the competence of human resources and motivation by the Head BPLH to paa employees, will be believed to be near optimal performance of employees at the Environmental Management Agency of Tangerang City. To meet the needs of clean air or oxygen for the people living in the city of Tangerang, Tangerang City Government shall have to be progressive in the budget provision for the supply of green open space felt very minimal in Kota Tangerang compared to the total population and the growth of motor vehicles that emit carbon gase